2017
DOI: 10.21595/vp.2017.19465
|View full text |Cite
|
Sign up to set email alerts
|

Research on consumption prediction of spare parts based on fuzzy C-means clustering algorithm and fractional order model

Abstract: Abstract. In order to achieve the non-stationary de-noising signal effectively, and to solve the prediction of less sample, a hybrid model composed of FCCA (Fuzzy C-means clustering algorithm) and FOM (Fractional Order Model) was constructed. The degree of each data point was determined by FCCA to de-noise and the order cumulative matrix was extended to fractional cumulative matrix, so that the fractional order cumulative grey model was established to make forecasting. The results of numerical example showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Guo et al 84 proposed the maintenance equipment support demand prediction steps based on I'SO-BPNN. Chen et al 85 considered the noise in consumption series, proposed a prediction method combining fuzzy C-means clustering algorithm and fractional order model, the result showed that the relative error and average relative error of the proposed method are less than EWT-BPNN.…”
Section: Machine Learning Of Spare Parts Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al 84 proposed the maintenance equipment support demand prediction steps based on I'SO-BPNN. Chen et al 85 considered the noise in consumption series, proposed a prediction method combining fuzzy C-means clustering algorithm and fractional order model, the result showed that the relative error and average relative error of the proposed method are less than EWT-BPNN.…”
Section: Machine Learning Of Spare Parts Predictionmentioning
confidence: 99%
“…Artificial neural network [76][77][78] Back-propagation neural network [81][82][83][84][85] demand patterns. It should be noted that the above method is limited by the assumptions of METRIC theory.…”
Section: Nonlinear Systemmentioning
confidence: 99%